INVENTION OF DIGITAL SWITCH THROUGH MOBILE APP TO UPDATE NEW PHONE NUMBER - Varadhan, Sriram (MATTER: International Journal of Science and Technology, 2018)
With the rapidly advancing technology we are in the need of some unique applications that will help us to make our lives easier. The number of mobile Apps available has grown-up massively over the past few years. With the smartphones and Internet have taken up most of our daily lives, very few Apps among millions are really serving our purposes (Robert, 2017). One of the major pain point in Telecommunication sector is, when we change our phone number, the process of updating the new number to all contacts is still outdated and needed automation. By carefully examining the pain point, we have innovated LetzwApp design. LetzwApp is a unique, innovative product for the Telecommunication IT markets because it transcends the connectivity problems that other providers have. Now, as a mobile customer, you can enjoy the full efficiency of your mobile, without the worry of losing important prospects when you change your number (Vishaka, 2017).